Weight suppression uniquely predicts body fat gain in first-year female college students. (January 2019) - Lowe, Michael R.; Marti, C. Nathan; Lesser, Elin Lantz; Stice, Eric
Abstract: Identifying predictors of increases in weight (or in fat mass) is important for understanding the genesis of obesity and for the design of prevention programs. We examined the predictive utility of 6 variables that have been predictive of weight gain in past research: depression, disinhibition, family history of overweight, body dissatisfaction, self-reported dieting and weight suppression (the difference between highest past and current weight). Percentage fat gain was evaluated with DEXA. We tested these variables as predictors of fat gain two years later in 294 female first-year students who were selected to have characteristics associated with future weight gain. Participants were categorized as weight stable or weight gainers at the two-year follow-up and logistic regression was used to evaluate the independent predictive ability of the 6 variables. Baseline body fat was entered as a covariate and predicted fat gain, as expected. The only significant predictor of the 6 tested was weight suppression, with those gaining weight showing greater weight suppression at baseline. Previous research has supported weight suppression as a robust predictor of future weight gain mostly among individuals with eating disorders. The current study indicates that weight suppression is a predictor of long-term fat gain among nonclinical female first-year students who were overwhelmingly in a healthy weight range. Highlights: The ability to predict weight gain is important for obesity prevention. Study examined 6 variables that have previously predicted weight gain. Only weight suppression was independent predictor of fat gain over two years.